2021
DOI: 10.3390/vaccines9080894
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Gemogenovatucel-T (Vigil) Survival and Molecular Signals of Immune Response in Recurrent Ovarian Cancer

Abstract: Aim: To determine the relationship between gene expression profile (GEP) and overall survival (OS) by NanoString following treatment with Vigil. Patients and Methods: Recurrent ovarian cancer patients (n = 21) enrolled in prior clinical trials. Results: GEP stratified by TISHIGH vs. TISLOW demonstrated OS benefit (NR vs. 5.8 months HR 0.23; p = 0.0379), and in particular, MHC-II elevated baseline expression was correlated with OS advantage (p = 0.038). Moreover, 1-year OS was 75% in TISHIGH patients vs. 25% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Functional immune activation of Vigil in correlation with clinical benefit has been demonstrated via ELISPOT assay [ 18 , 19 ]. Moreover, Vigil appears to increase CD3+/CD8+ T cell circulation in advanced solid tumor patients and expands MHC-II expression activity, as determined by NanoString analysis, in correlation with clinical benefit [ 20 , 21 ]. Safety and evidence of efficacy of Vigil has been evaluated in several tumor types in addition to ovarian cancer [ 18 , 19 , 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional immune activation of Vigil in correlation with clinical benefit has been demonstrated via ELISPOT assay [ 18 , 19 ]. Moreover, Vigil appears to increase CD3+/CD8+ T cell circulation in advanced solid tumor patients and expands MHC-II expression activity, as determined by NanoString analysis, in correlation with clinical benefit [ 20 , 21 ]. Safety and evidence of efficacy of Vigil has been evaluated in several tumor types in addition to ovarian cancer [ 18 , 19 , 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of Vigil relationship to BRCA1/2 -wt, HRP and TP53 mutation ( p53 -mu) subpopulations revealed correlation to clinical benefit 5 7 , 19 , 20 . These subpopulations were explored via KM analysis to assess the effect of combination biomarkers BRCA1/2 -wt, HRP, p53 -mu and genes identified as significant following multivariate analysis in this study on Vigil and placebo treatment effects as measured by OS and RFS.…”
Section: Methodsmentioning
confidence: 97%
“…Nevertheless, we have studied patient subpopulations most sensitive to Vigil therapy based on molecular profile using NanoString assessment, and demonstrated that TIS high score (tumor inflammation score) and MHC-II expression correlated with ELISPOT reactivity and clinically to OS and RFS 19 . Likewise, using NanoString technology to assess OS and RFS in patients enrolled in the VITAL study 20 , we showed marked benefit in patients with BRCA1/2 -wt and HRP profiles and improved outcomes in patients whose tumors had mutant TP53 ( p = 0.0013).…”
Section: Introductionmentioning
confidence: 99%
“… 54 Vigil has demonstrated induction of circulating mononuclear cell increase and gIFN production to autologous tumor via ELISPOT study. 55 - 57 Moreover, increase in circulating CD8+ cells has been observed following Vigil therapy. 57 …”
Section: Discussionmentioning
confidence: 99%